Crop improvement of coriander (Coriandrum sativum L. subsp. indicum var. indicum.) through crossing - Naidu, K Giridhar, S Suryakumari, C Sarada, L N (Journal of Spices and Aromatic Crops, 2016)
Coriander is the most important seed spice crop in India. Selection is the most common breeding procedure used in coriander and crossing is non-existent. The present study was conducted to promote crossing as a breeding technique in coriander. It was found that coriander was protandrous and the sex ratio was 1.75 to 2.07. The stigma was receptive from the 3rd day to 6th day of anthesis indicating that artificial pollination on emasculated florets must be done repeatedly on 3rd and 4th day of anthesis. Pollen was viable for two days in the field. Fresh pollen can be stored in incubator at 25oC for three weeks with 88% retention of viability. Emasculation of florets was carried out with the help of binocular loupe. Emasculation either in the morning before anthesis or previous day evening was found to be suitable. For demonstrating the technique, four parents were reciprocally crossed. Only three crosses were successful indicating the differences in combining ability of the parents. Mean success among the crosses was 23%, fruit set among the florets varied from 9.52-83.3% depending on the cross combination.